Social entrepreneurs : can they change the world? - Thompson, Marcus, ....-; Mawson, Suzanne, ....-; Martin, Frank, 1946- (London : Palgrave, 2017)
This core adoptable textbook equips students with the tools needed to create and manage a successful social enterprise and provides an excellent balance between theory and practice. Taking a highly engaging and focused approach, Social Entrepreneurs explores what it takes for entrepreneurs to translate their ambition and vision into an organisation that is targeted and socially meaningful. This new second edition shows how theories, models and concepts within entrepreneurship, business strategy and international marketing can be adapted to create high-impact social ventures that will deliver both positive impact and commercial success. Written by a team of experienced instructors and researchers, Social Entrepreneurs is ideal for students taking social entrepreneurship and social enterprise modules at undergraduate, postgraduate and MBA level. This textbook is also an essential companion for existing ventures to scale up and increase social impact locally, nationally or internationally.
Keywords: Management; ethisch ondernemen